SPATIAL DIFFERENCES IN THE NUMBER OF APPLICATIONS FOR PAYMENTS UNDER THE EU COMMON AGRICULTURAL POLICY SUBMITTED BY AGRICULTURAL HOLDINGS IN POLAND OVER THE YEARS 2002–2010 - Rudnicki, Roman (Quaestiones Geographicae, 2013)
This article offers a spatial analysis of the number of applications submitted by agricultural holdings in Poland for funds under the European Union’s Common Agricultural Policy over the years 2002-2010 (a total of 874 thous. applications, Table 1). This activity was characterised by dividing the assistance means obtained into measures intended to improve: the natural environment (Table 2, Fig. 1), the agrarian-demographic structure (Table 3, Fig. 2), the technical equipment of farms (Table 4, Fig. 3), and their income situation (Table 5, Fig. 4). The above measures are also shown jointly (Table 6, Fig. 5) and spatial differences in their structure are presented (Table 7, Figs 6 and 7). The analysis showed there to be wide territorial differences among agricultural holdings in Poland in terms of the total number and structure of the CAP measures they implemented.